Peran Religiusitas dan Optimisme terhadap Kesejahteraan Psikologis pada Remaja - Harpan, Abang (EMPATHY Jurnal Fakultas Psikologi, 2015)
ABSTRACTThis research aims to investigate the role of teenagersâ religiousness and optimism in their psychological well-being. This research sample was established by applying incidental sampling in which involving 152 students at SMU N 1 Turi, Sleman. The teenagersâ religiousness, optimism, and psychological well-being were measured by using religiousness scale, optimism scale, and psychological well-being scale with Likert scale as the model. The gathered data were analyzed by using path analysis. This analysis was done by using AMOS 21 and SPSS 17.0. The statistical results show that there was compatibility between the theoretic model, which consisting religiousness and optimism, and the empirical model in describing the psychological well-being. Psychological well-being that was described by optimism was 18.5 percent while the 81.5 percent was described by the other variables outside the research variables. Psychological well-being that was described by optimism and religiousness was 36.69 percent while the other 63.31 percent was described by the other variables that were not described in this research. There was direct role of religiousness in optimism. There was no direct role of religiousness in psychological well-being. There was direct role of optimism in psychological well-being. The optimism could not mediate between the religiousness and psychological well-being.Key words: religiousness, optimism, psychological well-being